Changes in intensive care unit nurse involvement in end of life decision making between 1999 and 2016: Descriptive comparative study. (February 2022) - Benbenishty, Julie; Ganz, Freda DeKeyser; Anstey, Matthew H.; Barbosa-Camacho, Francisco Jose; Bocci, Maria Grazia; Çizmeci, Elif Ayşe; Dybwik, Knut; Ingels, Catherine; Lautrette, Alexandre; Miranda-Ackerman, Roberto Carlos; Estebanez-Montiel, Belén; Plowright, Catherine; et al.
Abstract: Objective: Comparison of nurse involvement in end of life decision making in European countries participating in ETHICUS I- 1999 and ETHICUS II- 2015. Methodology: This was a prospective observational study of 22 European ICUs included in the ETHICUS-II and I. Data were collected as per the ETHICUS-I and ETHICUS-II protocols. Four questions within the ETHICUS protocols related to nurse involvement in end of life decision making were analyzed. This is a comparison of changes in nurse involvement in end of life decisions from 1999 to 2015. Setting: International e-based questionnaire completed by an intensive care clinician when an end of life decision was performed on any patient. Subjects: Intensive care physicians and nurses, no interventions were performed. Measurements: A 20 question survey was used to describe the decision making process, on what basis was the decision made, who was involved in the decision making process, and what precise decisions were made. Results: A total of 4592 cases from 22 centres are included. While there was more agreement between nurses and physicians in ETHICUS-I compared to ETHICUS-I, fewer discussions with nurses occurred in ETHICUS-II. The frequency of end of life decisions that were discussed with nurses decreased in all three regions between ETHICUS-I and ETHICUS-II. Conclusion: Based on the results of the current study, nurses should be further encouraged to increase their involvement in end of life decision-making, especially those in southern Europe.